2005 Guidelines on targets for solute and fluid removal in adults being treated with chronic peritoneal dialysis: 2019 Update of the literature and revision of recommendations. Issue 3 (May 2020) - Boudville, Neil; de Moraes, Thyago Proença
Background: The International Society for Peritoneal Dialysis guidelines for small solute clearance and fluid removal in peritoneal dialysis (PD) were published in 2005. The aim of this article is to update those guidelines by reviewing the literature that supported those guidelines and examining publications since then. Methods: An extensive search of publications was performed through electronic databases and a hand search through reference lists from the existing guideline and selected articles. Results: There have been no prospective intervention trials to inform the area of small solute clearance in PD since the publication of the original guideline in 2005. The trials to date are largely limited to a few prospective cohort studies and retrospective studies. These have, however, consistently demonstrated that residual renal function (RRF) is more often associated with patient outcome than peritoneal clearance. One of the few randomised controlled trials performed in this area does suggest that a weekly Kt / V of 2.27 ± 0.02 provides no statistically significant survival advantage over a weekly Kt / V of 1.80 ± 0.02. The lower limit of Kt / V is unknown but there is weak evidence to suggest that anuric people doing PD should have a weekly Kt / V of at least 1.7. Conclusions: There continues to be very poor evidence in the area of small solute clearance and fluid removal in PD. The evidence that exists suggests that RRF is more important than peritoneal clearance and that there appears to be no survival advantage in aiming for a weekly Kt / V >1.70.